2016
DOI: 10.5032/jae.2016.03145
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Source: A Mixed Methods Analysis of Undergraduate Students’ Attitudes Toward Genetically Modified Food

Abstract: Even though science says genetically modified (GM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Young consumers and those with higher levels of education were likely to be aware of modern farming practices and concerned with animal welfare (Clark et al, 2016). However, research also has supported Rogers' (2003) conclusion that the effect of age on innovation adoption was inconclusive as studies regarding GM science perceptions have found conflicting results regarding age and attitude (Antonopoulou et al, 2009;Ruth et al, 2016). Makki et al (2013) explored differences in socioeconomic status and water conservation while showering.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young consumers and those with higher levels of education were likely to be aware of modern farming practices and concerned with animal welfare (Clark et al, 2016). However, research also has supported Rogers' (2003) conclusion that the effect of age on innovation adoption was inconclusive as studies regarding GM science perceptions have found conflicting results regarding age and attitude (Antonopoulou et al, 2009;Ruth et al, 2016). Makki et al (2013) explored differences in socioeconomic status and water conservation while showering.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Prior research regarding ANR communication determined demographic characteristics, such as gender, age, and race/ethnicity, influence people's perceptions of agricultural and life science topics (Antonopoulou, Papadas, & Targoutzidis, 2009;Clark, Stewart, Panzone, Kyriazakis, & Frewer, 2016;Conko & Prakash, 2005;Gaskell, 2003;Hall & Moran, 2006;Irani, Sinclair, & Malley, 2001;Makki, Stewart, Panuwatwanich, & Beal, 2013;McKendree, Croney, & Widmar, 2014;Moon & Balasubramanian, 2001;Ruth, Gay, Rumble, & Rodriguez, 2016). Gender has been associated with influencing perceptions of ANR issues, and Clark et al (2016) found that women were more likely than men to be concerned with animal welfare issues.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Limiting exposure to different values and beliefs could cause faculty to not acknowledge the legitimacy in others' views toward science (Huckfeldt et al, 2004;Price et al, 2002). Additionally, only communicating to one specific type of group could further polarize attitudes toward agricultural and basic science topics across demographics groups (Antonopoulou et al, 2016;Makki et al, 2013;McKendree et al, 2014;Ruth et al, 2016). However, the echo chamber questions did not ask about who faculty spent time with professionally, and faculty may be exposed to different opinions and values through those connections.…”
Section: Explore Uf/ifas Tenure-track Faculty's Communication Channementioning
confidence: 99%
“…In addition to producing research that is not relevant to the institutions' stakeholders, lack of communication across diverse audiences could lead to varying levels of attitudes and knowledge related to science. Research has found differences in attitude and acceptance in agricultural and natural resource topics related to gender, age, income, and race/ethnicity (Antonopoulou, Papadas, & Targoutzidis, 2009;Clark, Stewart, Panzone, Kyriazakis, & Frewer, 2016;Makki, Stewart, Panuwatwanich, & Beal, 2013;McKendree, Croney, & Widmar, 2014;Ruth, Gay, Rumble, & Rodriguez, 2016). Women have been found to be more interested in topics related to health, medicine, and food safety, but men have been more interested in science and technology topics (Kennedy & Funk, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Related research on consumer opinions of another emerging technology, nanotechnology, suggests that once consumers do become more informed, they may become polarized on the issues of risk based on cultural associations, rather than knowledge (Kahan, Braman, Slovic, Gastil, & Cohen, 2009). Current research in agricultural education on biotechnology attitudes (Ruth, Rumble, Gay, & Rodriguez, 2016;Wingenbach, Rutherford, & Dunsford, 2003) may focus on undergraduates and often undergraduates at land-grant institutions, which may not be representative of the U.S. population as a whole.…”
mentioning
confidence: 99%